Funk nacional: sons de um movimento em construção - Vaz, Otacilio Evaristo Monteiro (2013)
This research examines some strategies promoted by the Funk de Raiz movement, specifically relating to its operations through radio programs, aiming to reformat a supposedly uniform and negative view of the funk culture, mainly disseminated by the news and police reports. The program Funk Nacional, produced by the Association of Professionals and Friends of Funk (Apafunk) and broadcast by Nacional Radio of Rio de Janeiro, brings a differentiated message of funk, seeking new viewpoints of the movement, triggered by various resources such as the performance of the presenters, the constituent units of the musical discourse, in its articulation with body movements, such as rhythm and intonation, and semantic-political mechanisms expressed in the lyrics. Although manifested in a larger set of strategies, which define them in their entirety, the programs analyzed allow us to glimpse the play of voices and presumed viewpoints in the way they perceive themselves as being seen by society, how they see the other lines of the funk culture and therefore, the way they try to legitimize their own visibility. For that, we turn to theoretical fundaments extracted from cultural studies, sociology and social semiotics, having as main sources works by Eric Landowski on regimes of visibility; Norbert Elias and Howard Becker on the concept of established ones and outsiders; Adriana Lopes, Hermano Vianna and Simone de Sá Pereira on studies about the funk from Rio de Janeiro. The tools of analysis encompassed the universe of three programs registered through the Internet, in the years of 2011, 2012 and 2013. From the analysis made based on the aforementioned criteria and scholars, we found that the Funk Nacional program highlights specific forms of integration to collective axiologies, while incorporating the other's stance - "society" - on how to conceive other currents of funk.